Hvad siger loven? - om retsreglerne som kommunikative handlinger - Schack, Jørgen (HERMES - Journal of Language and Communication in Business, 1990)
Law of contract is concerned with what may be called "the promising game" as it contains the rules which constitute the act of "making a promise". Law of contract thus resembles the traditional speech act theory of Austin and Searle. According to speech act theory, to primise is to utter a conventional formula in approproate circumstances: what makes an utterance a promise are certain conventional rules involving features of the context.